QUALITY OF LIFE IN CAREGIVERS OF PEDIATRIC PATIENTS WITH CEREBRAL PALSY AND GASTROSTOMY TUBE FEEDING - Aldvan Alves FIGUEIREDO; Elizete Aparecida LOMAZI; Maria Augusta MONTENEGRO; Maria Angela BELLOMO-BRANDÃO (Arquivos de Gastroenterologia, 2020)
ABSTRACT BACKGROUND: Cerebral palsy is the most common cause of physical disability in childhood. Caregivers of patients presenting tetraparesis cerebral palsy (TCP) and gastrostomy tube feeding (GTF) were selected for this study because both conditions represent a great demand for their caregivers. OBJECTIVE: To describe the quality of life related to the state of health of caregivers of patients with TCP who were fed by gastrostomy, to assess the results linked to the mental health of these caregivers, to compare our data with data from other studies on children with cerebral palsy without gastrostomy and to evaluate the possible interference of gastrostomy in the quality of life. METHODS: A number of 30 major caregivers were interviewed and assessed. Quality of life and mental health tools applied and analyzed only for caregivers were: Medical Outcomes Study (MOS) 36-item Short Form Health Survey (SF-36), WHOQOL-BREF and Beck scales. Other information (age, gender, marital status, number of residents per household and psychological support) was evaluated. The Spearman’s rank correlation coefficient was used to analyze. A 5% significance level was adopted. RESULTS: Results obtained through questionnaires are as follows: moderate hopelessness in 20% of caregivers (the higher the number of residents per household the higher the level of caregiver’s hopelessness); moderate and severe anxiety in 33.33% of the sample studied; moderate and severe depression identified in 46.67% of interviewed caregivers; health-related quality of life of caregivers of patients with TCP were found to be below world averages; no significant figures for suicide potential were noted for the population under this study. CONCLUSION: The HRQOL of caregivers of TCP patients who were fed by gastrostomy is below the average of the general population. Our results are very similar to those found in other studies that evaluated caregivers of patients with cerebral palsy with different degrees of neurological impairment and no report of using GTF, suggesting that the presence of gastrostomy did not negatively interfere with the caregiver’s HRQOL.